PEMBERDAYAAN MASYARAKAT TANI MELALUI PROGRAM KELUARGA HARAPAN (PKH) DI DESA MAEK KECAMATAN BUKIT BARISAN KABUPATEN LIMAPULUH KOTA PROVINSI SUMATERA BARAT - Marsisvi, Neli; Maemunaty, Titi; Wilson, Wilson (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The formulation of the problem in this study is: How to plan, organize, implement, and monitor participatory evaluation of the empowerment of farming communities through the family hope program (PKH) in Maek Village, Bukit Barisan District, Limapuluh Kota Regency, West Sumatra Province? In accordance with the formulation of the problem, the purpose of this research is to find out the planning, organizing, implementing, and monitoring of participatory evaluation of farmer community empowerment through the family hope program (PKH) in Maek Village, Bukit Barisan District, Limapuluh Kota Regency, West Sumatra Province. This type of research is descriptive naturalistic with a qualitative approach. The subjects of this study were 6 people, the technique of retrieving data sources was snowball sampling. The instrument of this study uses participatory observation, interviews and documentation. The results of the analysis carried out can be concluded that management of farmer community empowerment has 4 stages, namely planning, organizing, implementing, and monitoring participatory evaluations.Key Words: Empowerment, Farmers Community, Hope Family Program